Paul, Josephus, and the Judean Nationalistic and Imperialistic Policy of Forced Circumcision - Howell Chapman, Honora ('Ilu. Revista de Ciencias de las Religiones, 2006)
This paper analyzes the background for the Judean nationalistic and imperialistic policy of forced circumcision as it developed through the Hasmonean period, and then how this policy should be taken into account when examining the issue of circumcision in the works of Paul, especially the Letter to the Galatians, and also in Josephus’ writings. Both of these first-century Jews rejected forced circumcision of Gentiles when creating and maintaining their own communities, and I argue that it is essential to view their respective choices as a direct response to the remembered history of the Judean policy of forced circumcision. Previous scholarship on this issue has focused mainly on the question of conversion and has not made a direct connection between Paul, Josephus, and the Judean policy of forced circumcision.